PEMIKIRAN METODOLOGIS A. MUKTI ALI TENTANG PENELITIAN AGAMA - Rahmadi, Rahmadi (Jurnal Ilmu Ushuluddin, 2015)
In Indonesia, it will be said that A.Mukti Ali is a pioneer in introducing religious studies. A.Mukti Ali realized thatreligious studies did not only need the scientific methods but they must also integrate with social approaches. He thoughtreligious studies should be conducted objectively without involving the apologists-polemical element as a basic concept. Infact, the use of the scientific method, social sciences, and objective attitude do not be certainly enough to understandreligious phenomenon, despite religious reflection must be involved and researchers must give their views too. All componentsmust be synthesized in order to produce a holistic and integral assessment of religious phenomenon. The integratedcomponents that needed in studying religious phenomenon is what be called by Mukti Ali as a scientific approach-cumdoctrinaire.This writing will discussed about A.Mukti Aliâs thoughts in the field of religious studies.